Analisis Percepatan Getaran Tanah dan Tingkat Kerentanan Tanah di Daerah Lampung - Septika Locita; Gurum Ahmad Pauzi; Amir Supriyanto (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2018)
The measurement of peak ground acceleration and ground vulnerability index in Lampung area has been done. This study aims to analyze the acceleration of ground vibration and ground vulnerability index with soil types namely, entisol, inceptisol and ultisol. The tool used to perform the measurement is the vibration meter VB-8213. The results of the analysis show that changes in the acceleration value of ground vibration and ground vulnerability have the same pattern of change with distance. The further distance to the vibration source the acceleration value of ground vibration and ground vulnerability index will be smaller. The greatest vibration acceleration value is found in ultisole and inceptisol soil type. The smallest vibration acceleration value of the soil type is entisol. While the value of ground vulnerability index for all types of soil entisol, inceptisol and ultisol have relatively small ground vulnerability index.